Justificação e racionalidade na decisão judicial tributária - Rodrigues, Rafael de Oliveira (2020)
This dissertation focus on the concentration of rationality of tax law within the principle of tax legality and whether this premise fits the current governmental standard in order to meet social demands. It is not unknown that the consolidated conception of statutes is a source of legitimacy for government tax actions. In this sense, the History has a myriad of facts in which the requirement of prior popular authorization for the implementation of the tax power has led to social upheavals and, consequently, to this consolidation of governmental standards. This social demand, which uprises the statute into a source of permission, sets the standard of state based on a completely separation of functions. At this point in history, the government is required to control its actions in order to avoid abuse - which, in the field of tax law, could turn community’s life unfeasible. However, society changes over time and, therefore, now requires more from the State. It is not enough to act within preset models. Government authorities are required to present themselves in a proactive manner, positively enforcing rights acknowledged worldwide as fundamentals. Right now, the legislative function is appraised in a way to recognize that it cannot do everything on its own. Therefore, the jurisdictional function is placed on the same level as the other branches in a way of collaborating with them (mostly with the Legislative) incisively participating in the realization of constitutional rights. That is a turning point to the Judiciary Branch, although, it is a very hard shift. On one hand, there is a considerable resistance from those who only understand the Judiciary as a branch whose attributions are to comply with the will of Legislative branch. On the other hand, there are those who believe the supremacy of the Constitution legitimizes everything, including the disregard of the statutes. Therefore, the comprehension of each one´s role is a fundamental task in order to find a model of state in which, at the same time, it could be compromised to fundamental rights and could hold the connection to the democratic and republican basis. In this sense, it is set a duty to Judiciary Power in developing the law, in a way of, through a rational discourse and justified actions, fitting into the idea conceived by the Legislative (although latent in the stature) within the social values which spring in significance when identified inside a specific set of facts. To achieve this scope, the comprehension of judicial decision, and more specifically the jurisprudence, under the perspective of the theory of precedent, presents a key tool to identify how the jurisdictional function deals with the decision reasoning and allows it to be adapted to the will of the tax legislative decision